Implementasi Sistem Pengelolaan Rekap Jual Beli pada Toko Busana - Aryasanti, Agnes; Wiharto, Yudi; Mufti, Mufti (Journal Software, Hardware and Information Technology, 2023)
The buying and selling recap management system is a system that can help manage buying and selling transactions in a business. The aim of implementing a sales and purchase recap management system at the Fashion Store is to increase store management efficiency, facilitate financial management, monitor inventory, and reduce errors in recording transactions. The method used is in the form of observation, interviews, and data analysis to collect the necessary data. Furthermore, designing and implementing a buying and selling recap management system at the Fashion Store. This system can record buying and selling transactions automatically and generate reports on sales, purchases, and profits easily and quickly. The results of the implementation of the sales and purchase recap management system show that this system can increase store management efficiency, reduce errors in transactions, facilitate stock and financial monitoring. This system also makes it easy for users to access buying and selling transaction data and generate reports automatically. In conclusion, the implementation of a sales and purchase recap management system at Clothing Stores provides significant benefits for store management and can be applied to various types of businesses to increase management efficiency and save time and costs required in store management.